Application of zirconium modified layered double hydroxide and calcination product for adsorptive removal of phosphate from aqueous solution. Issue 2 (21st August 2021) - Motandi, Mave Koko; Zhang, Zhaoran; Inkoua, Stelgen; Yan, Liangguo
Abstract: Layered double hydroxides (LDHs) have been designed and applied in environmental remediation based on their tunable physical structure and excellent chemical performance. To investigate the adsorption behavior of aqueous phosphate by the LDH‐based composite, zirconium‐modified Mg‐Al‐LDH (Zr‐LDH) was synthesized by the coprecipitation method, and subsequently calcined to obtain a layered double oxide (Zr‐LDO). Scanning electron microscopy, X‐ray diffraction, and Fourier transform infrared spectroscopy were used to describe the micromorphology, crystal structure, and functional groups of Zr‐LDH and Zr‐LDO, respectively. The as‐synthesized materials were subsequently selected as adsorbents to adsorb aqueous phosphate using batch equilibrium methods. The results showed that Zr‐LDH and Zr‐LDO can rapidly and efficiently reduce the phosphate concentration. The optimum dosage of LDH, Zr‐LDH, and Zr‐LDO was selected as 0.05 g. The adsorption efficiencies of Zr‐LDH and Zr‐LDO for phosphate were above 95% during the first 10 min. The experimental data agreed well with the pseudo‐second‐order equation, and the Langmuir and Freundlich equations. The maximum adsorption capacities of Zr‐LDH and Zr‐LDO were 99.35 and 80.33 mg/g, respectively. Moreover, the reaction process was spontaneous and endothermic. Zr‐LDH and Zr‐LDO have good reusability and selectivity, and are promising materials for aqueous phosphate removal. This work confirms that Zr‐LDH and Zr‐LDO can be selected as favorable sorbents to remove phosphate from wastewater.